Liver resection for a congenital intrahepatic portosystemic shunt in a child with hyperammonemia and hypermanganesemia: a case report - Yuichi Takama; Tetsuro Nakamura; Kenji Santo; Akihiro Yoneda (Surgical Case Reports)
Abstract Background Congenital portosystemic shunt (CPSS) is a rare malformation that leads to hyperammonemia, hypermanganesemia, and various symptoms. CPSSs are divided into intrahepatic and extrahepatic shunts. In patients with persistent CPSS including an intrahepatic portosystemic shunt (IPSS), early intervention to occlude the shunt reverses the associated complications. Case presentation The patient was a 1-year-and-7-month-old girl. She presented with hypergalactosemia and elevation of blood ammonia level (75 μg/dL) and total bile acid levels (68.2 μmol/L) during the neonatal period. Two IPSSs were detected using ultrasound and enhanced computerized tomography. Magnetic resonance imaging (MRI) at 1 year and 3 months of age showed abnormally high signal intensity in the pallidum of her brain. Spontaneous closure was not observed. We performed a right hepatectomy at 1 year and 7 months of age. The portal vein pressure was 16 mmHg after temporary occlusion of the right portal vein. Blood ammonia and serum manganese levels decreased immediately after the operation. The abnormal signal on brain MRI disappeared. She had a favorable course with no sign of recurrence of IPSS 5 years postoperatively. Conclusion Liver resection for an IPSS to control the symptoms of a portosystemic shunt is reasonable in a child for whom interventional radiological treatment is not indicated.